PENINGKATAN KUALITAS PEMBELAJARAN IPS MELALUI MODEL COOPERATIVE SCRIPT BERBANTUAN MEDIA POWERPOINT DI KELAS V SD NEGERI 011 DESA BARU KECAMATAN SIAK HULU KABUPATEN KAMPAR - Kadariya Kadariya (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2018)
This research is motivated by low student learning outcomes. The purpose of this study is to improve the quality ofsocial science learning through model cooperative script on the students of class V SD Negeri 011 Desa Baru. Thedesign of this study uses a classroom action research consisting of three cycles, each one-time meeting cycleincluding planning, execution, observation, and reflection. Technique of collecting data using test and nontesttechnique (observation, interview, documentation). The results showed that the skills of teacher cycle I score 21sufficient criterion, cycle II score 27 good criterion, and cycle III score 32 criteria very good; student activity cycleI score 17 with sufficient criteria, cycle II score 21 with very good criteria, and cycle III score 24 criteria is verygood; classical completeness of cycle I is 57%, cycle II to 70%, and cycle III to 87%. From the results of this studycan be concluded that the model coopertave script with media powerpoint in SD Negeri 011 Desa Baru has beenable to improve teacher skills, student activities, and student learning outcomes.